Unlocking Harmony: How Islamic Principles Revolutionize Sfaety and Inclusion for Special Needs Education - Dewanti, Dinda Rachma; Hermanto, Hermanto; Azizah, Nur (EDUPEDIA Publisher, 2024)
This research explores the role of Islamic leadership values in promoting inclusive education within a private junior high school in Yogyakarta, focusing on how these values influence the school's ability to provide a supportive and inclusive environment for students with special needs. The study is motivated by the growing recognition of inclusivity challenges in schools and the potential of Islamic leadership principles to address these challenges effectively. Using a qualitative case study approach, the investigation involved in-depth interviews and observations with key informants, including teachers, a school counselor, and the principal, to capture a multifaceted view of the implementation of tabligh (effective communication) and fathonah (intelligence) in fostering inclusivity.The findings reveal that the principal's application of Islamic leadership values, particularly through regular meetings, the buddy system, and Islamic speech sessions, significantly enhanced the school's inclusivity culture. These initiatives promoted better peer interactions, increased teacher and parental engagement, and offered a supportive network for students with special needs. However, challenges such as inconsistent implementation of inclusivity strategies and inadequate facilities were also identified. In conclusion, the study highlights the effectiveness of Islamic leadership values in enhancing inclusivity in education settings, underscoring the importance of tailored approaches to address the diverse needs of students. It suggests further research into adaptive inclusive practices and the impact of parental involvement, pointing towards a comprehensive approach to integrating cultural and religious values into educational leadership for fostering inclusivity.